Peran Kepemimpinan Kepala Pesantren dalam Meningkatkan Kedisiplinan dan Produktivitas Santri - Moh Mufid; Moh Rofiki (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research focuses on the role of the head of the pesantren in improving students' discipline and productivity at Nurul Jadid Islamic boarding school. The main focus of the research is how the leadership of the head of the pesantren, through exemplary behaviour, enforcement of regulations, and consistent supervision, can create a disciplined and productive educational climate. The research approach is qualitative, using a case study method. Data were collected through in-depth interviews, participatory observations, and document analysis, involving 12 respondents: the head of the pesantren, administrators, and students. Data analysis was conducted using the Miles and Huberman technique, which includes data reduction, data presentation, and conclusion drawing. The research results show that the leadership of the pesantren head has a significant influence in fostering students' discipline through daily examples and educational social control. The discipline that is subsequently formed encourages students' productivity in academic, spiritual, and social aspects. This research has important implications: leadership grounded in exemplary behaviour and religious values remains relevant in the modern era to strengthen character education. Moreover, this research enriches the literature on Islamic educational leadership by asserting that consistent leadership quality rooted in religious traditions can be a key factor in shaping a generation of disciplined, productive, and competitive santri.